Bioinspired temporal supramolecular polymerization. Issue 34 (22nd May 2018) - Dhiman, Shikha; Sarkar, Aritra; George, Subi J.
Abstract : Nature's fuel-driven approach as a generic concept for structural and temporal regulation over biomimetic synthetic supramolecular polymerization. Abstract : Thriving natural systems precisely regulate their complex chemical organizations in space and time by recruitment of a complex network of fuel-driven, kinetically controlled, out-of-equilibrium transformations. Indeed this provides an active, adaptive and autonomous smart actions & functions. In contrast, synthetic systems exhibit simpler behavior owing to thermodynamically driven supramolecular polymerization with no temporal modulation of spatial organization. Stimulated by an outstanding control that nature demonstrates, a drive towards artificial out-of-equilibrium systems with the ambition to program activation and duration of structural transformations has emerged. To realize this vision, overwhelming efforts across the globe have been initiated to design temporally programmed synthetic supramolecular polymers. In an attempt to contribute to this trending field, our supramolecular chemistry group has thoroughly investigated a structure–property relationship that determines the mechanism of supramolecular polymerization. Exploiting these mechanistic insights, along with a bio-inspired fuel-driven enzyme mediated approach, we further attempted to program supramolecular polymers in both structural and temporal regimes. We believe, nature is the inspiration to the current era challenges and it also provides with the solution, a fuel-driven approach to address these. In this account, we shall discuss the efforts made by our group to build generic concept to create temporally programmable supramolecular polymers.